2016
DOI: 10.1080/02640414.2016.1210194
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of judo breakfall for osoto-gari: Considerations for head injury prevention

Abstract: Previous studies suggest that increasing the skill level of judokas will decrease the number of head injuries sustained during judo. However, the kinematics are poorly understood, making it difficult to establish an effective breakfall teaching programme. Therefore, we studied the kinematic parameters of breakfall for osoto-gari to identify the risk of judo-related head injuries by comparing experienced and novice judokas. This information will provide insight into developing a better prevention plan for judo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…Regarding the comparison between NE-A and E-A, the lack of difference in a p is in line with results of Koshida et al 44 that report no differences in linear acceleration during backward falls between experienced and novice judoka. The absence of differences in u f between experienced and novice judoka while being thrown with o-soto-gari is in line with findings of Koshida et al 11 They found also lower neck extension moment in experienced compared to novice judoka and suggest that neck extension moment reflects judoka skill level; thereby, this parameter should be considered in further analysis when experience level is investigated. 11 Greater u e was found for NE-A compared to E-A in ouchi-gari, indicating that novice should be accurately being taught important components such as controlling the neck in order to prevent head risks.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Regarding the comparison between NE-A and E-A, the lack of difference in a p is in line with results of Koshida et al 44 that report no differences in linear acceleration during backward falls between experienced and novice judoka. The absence of differences in u f between experienced and novice judoka while being thrown with o-soto-gari is in line with findings of Koshida et al 11 They found also lower neck extension moment in experienced compared to novice judoka and suggest that neck extension moment reflects judoka skill level; thereby, this parameter should be considered in further analysis when experience level is investigated. 11 Greater u e was found for NE-A compared to E-A in ouchi-gari, indicating that novice should be accurately being taught important components such as controlling the neck in order to prevent head risks.…”
Section: Discussionsupporting
confidence: 87%
“…The absence of differences in u f between experienced and novice judoka while being thrown with o-soto-gari is in line with findings of Koshida et al 11 They found also lower neck extension moment in experienced compared to novice judoka and suggest that neck extension moment reflects judoka skill level; thereby, this parameter should be considered in further analysis when experience level is investigated. 11 Greater u e was found for NE-A compared to E-A in ouchi-gari, indicating that novice should be accurately being taught important components such as controlling the neck in order to prevent head risks. 44 Finally, greater _ v p , longer t i , and greater GSI for NE-A compared to E-A in o-soto-gari pointed out that being thrown with o-soto-gari may be more challenging that being thrown with other techniques, as suggested by Koshida et al 12 This aspect should be considered when novice judoka are trained.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…One Takeshi KAMITANI* , ***, Natsuko ONIDANI*, Masaki OMIYA** and Atsuhiro KONOSU**** factor often cited for such injuries is the use of the unskilled falling technique (ukemi) (Nagahiro et al, 2011;Kamitani et al, 2013). In fact, neck extensions and large angular head rotation problems have been noted in experiments designed to analyze the body movements of beginners executing the ukemi technique (Kamitani et al, 2014, Koshida et al, 2017.…”
Section: Introductionmentioning
confidence: 99%